2022
DOI: 10.3390/ani12223109
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Carboplatin in Combination with Low-Dose Cyclophosphamide in Female Dogs with Mammary Carcinoma

Abstract: This prospective study aimed to evaluate the effect of metronomic cyclophosphamide on carboplatin’s tolerability, efficacy, and pharmacokinetics in dogs with mammary carcinoma. Sixteen female dogs with mammary carcinoma were divided into groups: 300 mg/m2 intravenous (i.v.) carboplatin therapy (G1 = 8) or 300 mg/m2 i.v. carboplatin which was associated with 12.5 mg/m2 oral cyclophosphamide in a metronomic regimen (G2 = 8). The investigated animals underwent a clinical evaluation, a mastectomy, a carboplatin ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…In line with that, De Campos et al and Machado et al showed that metronomic cyclophosphamide following surgery and four (59) to six (64) cycles of intravenous carboplatin resulted in a better outcome than surgery alone (59) or surgery plus conventional chemotherapy only (59,64). Interestingly, the only adjuvant drug that allowed a better prognosis in these patients when added instead of cyclophosphamide was thalidomide, according to one of these studies (59).…”
Section: Canine Mammary Carcinomamentioning
confidence: 64%
See 3 more Smart Citations
“…In line with that, De Campos et al and Machado et al showed that metronomic cyclophosphamide following surgery and four (59) to six (64) cycles of intravenous carboplatin resulted in a better outcome than surgery alone (59) or surgery plus conventional chemotherapy only (59,64). Interestingly, the only adjuvant drug that allowed a better prognosis in these patients when added instead of cyclophosphamide was thalidomide, according to one of these studies (59).…”
Section: Canine Mammary Carcinomamentioning
confidence: 64%
“…In fact, several authors have suggested the possibility of an additive and synergistic effect of this combined use, which could potentially improve the prognosis of these patients ( 57 , 72 ). The two intravenous drugs that have been most commonly used in a MTDC setting, in combination with MC, are doxorubicin ( 57 , 71 , 72 , 74 ) and carboplatin ( 64 , 71 ). Additionally, tyrosine kinase inhibitors have also been prescribed in association with metronomic cyclophosphamide, particularly oral toceranib at a dose of 2.4 to 2.75 mg/kg every other day or three times a week ( 44 , 56 , 65 , 80 , 90 ).…”
Section: Metronomic Chemotherapy In Veterinary Oncologymentioning
confidence: 99%
See 2 more Smart Citations
“…Spontaneous mammary tumors in female dogs are considered models for the study of breast cancer in women ( 1 , 2 , 22 25 ). Additionally, such tumors are frequent among the canine population, and more than 50% of cases are malignant ( 1 , 6 , 25 , 26 ), considering that mammary carcinoma in mixed tumors (CMT) has variable malignancy potential depending on histological grade ( 1 ). Nevertheless, there are few studies related to the expression of GATA-3 in mammary neoplasms of female dogs.…”
Section: Introductionmentioning
confidence: 99%